2021
DOI: 10.1016/j.ijnss.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors that motivate nursing students to engage in skills practice in a laboratory setting: A descriptive qualitative design

Abstract: Objectives The aim of this study was to explore factors that motivate students to engage in skills practice in a laboratory setting, and to identify their motivation types and the regulatory styles. Methods Semi-structured interviews were conducted with 23 nursing students from three universities between November 2017 and January 2018. A thematic analysis was used to identify factors associated with students’ motivation to engage in skills practice in a laboratory. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Bodkyn and Stevens 10 argued that the teacher's competence is an important factor in sustaining the motivation that influences SDL. Pedagogical approaches, for example, can have an impact on student motivation, which is something that nurse educators must keep in mind when planning their lessons 55 . Akbar et al 9 in their analysis of Southeast Asian students, where two of the three countries in our sample are geographically situated, they identified three prerequisites for a successful SDL: learner characteristics (whether they have previous SDL knowledge), the environment in which students may develop their SDL ability, and the instructor‐learner relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Bodkyn and Stevens 10 argued that the teacher's competence is an important factor in sustaining the motivation that influences SDL. Pedagogical approaches, for example, can have an impact on student motivation, which is something that nurse educators must keep in mind when planning their lessons 55 . Akbar et al 9 in their analysis of Southeast Asian students, where two of the three countries in our sample are geographically situated, they identified three prerequisites for a successful SDL: learner characteristics (whether they have previous SDL knowledge), the environment in which students may develop their SDL ability, and the instructor‐learner relationship.…”
Section: Discussionmentioning
confidence: 99%
“…During the online learning process in the Covid-19 pandemic, according to the study results, the level of learning motivation showed that most students had 65% high learning motivation and 8.3% very high motivation, 20% moderate, and 6.7% low motivation. It meant that motivation to learn lead to the learning process and ensure the continuity of these activities effectively and maximally (Laothong & Cheng, 2017;Nakayoshi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the 5.0 industrial revolution had combined essential elements in the 21st century, namely humans and technology (Mukhalalati et al, 2020). The use of technology also enabled distance learning to emerge and encouraged more significant innovation in creating teaching methods inside and outside the classroom (Nakayoshi et al, 2021). Therefore, through the use of technology during online learning, it was hoped that specific classrooms and time would no longer limit the current learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Once they begin training, however, trainees may be unlikely to spontaneously frame their engagement in training activities as helping them make progress toward their life goals. Rather, their life goals may fade into the background as they focus on achieving shorter-term goals tied to looming assessments and assignment deadlines (Carver and Scheier, 1998;Nakayoshi et al, 2021). That is, their shorter-term goals may become functionally superordinate in guiding their actions (Carver and Scheier, 1998).…”
Section: Prompting Life Goal Framing: a Proposed Design Strategymentioning
confidence: 99%
“…In other words, effective prompts emphasize that an activity affords a set of professional actions that, when enacted, serve a trainee's life goals. Trainees may spontaneously make the first link between a training activity and a set of professional skills (Nakayoshi et al, 2021). However, they may not regularly extend this link to their life goals, unless prompted to do so.…”
Section: Prompting Life Goal Framing: a Proposed Design Strategymentioning
confidence: 99%